Association of HLA-A3 and HLA-B14 antigens with idiopathic haemochromatosis. Issue 5 (May 1976) - Simon, M; Bourel, M; Fauchet, R; Genetet, B
Abstract : The frequency of HLA-A3 and HLA-B14 antigens was significantly higher in a series of 51 patients with idiopathic haemochromatosis than in a control group, being respectively 78-4 versus 27-0% and 25-5 versus 3-4%. This finding strongly supports the suggestion that idiopathic haemochromatosis is a genetic disease and suggests that the gene(s) responsible for the disease may be linked to the histocompatibility genes.